Association of IL-4 and IL-18 genetic polymorphisms with atopic dermatitis in Chinese children - Shi, Jianrong; He, Lin; Zheng, Huiwen; Li, Wei; Huang, Shuangshuang; Li, Yunling; Tao, Ran (Frontiers in Pediatrics, 2023)
Background: Atopic dermatitis (AD) is a common chronic inflammatory skin disease, adversely affecting nearly 20% of the pediatric population worldwide. Interleukin-4 (IL-4) and interleukin-18 (IL-18) are considered to be involved in the pathogenesis and development of AD. The aim of this study was to investigate the association of IL-4 and IL-18 gene polymorphisms with the susceptibility and severity of AD in Chinese children. Methods: Six candidate single nucleotide polymorphisms (SNPs) in IL-4 and IL-18 genes were genotyped through multi-PCR combined with next-generation sequencing in 132 AD children and 100 healthy controls, and all the analyses were performed on blood genome DNA. Results: The frequencies of G allele, CG genotype and CG+GG genotype of IL-4 rs2243283, as well as the haplotype IL-4/GTT (rs2243283-rs2243250-rs2243248) were all significantly decreased in AD patients compared with the controls [G vs C: P = 0.033, OR = 0.59; CG vs CC: P = 0.024, OR = 0.47; CG+GG vs CC: P = 0.012, OR = 0.49; GTT vs CCT: P = 0.011, OR = 0.65]. Moreover, the frequencies of A allele, AA genotype and AG+AA genotype of IL-18 rs7106524, along with the haplotype IL-18/CAA (rs187238-rs360718-rs7106524) were statistically increased in the severe AD patients (A vs G: P < 0.001, OR = 2.79; AA vs GG: P = 0.003, OR = 5.51; AG+AA vs GG: P = 0.036, OR = 2.93; CAA vs CAG: P = 0.001, OR = 2.86). Conclusions: Our findings suggested that genetic variation in IL-4 rs2243283 such as G allele, CG genotype and CG+GG genotype might confer the reduced susceptibility to AD in Chinese children. Furthermore, A allele, AA genotype and AG+AA genotype of IL-18 rs7106524 explored the strong association with severity in Chinese AD children.